EMPOWERMENT OF TUNAS BARU FARMER GROUP OF DENAI BIRD'S NEST VILLAGE THROUGH INCREASING ADDED VALUE AND UTILIZATION OF AGRICULTURAL PRODUCTION RESIDUES - Monika Andrasari; Syech Suhaimi; Nurmala Fitri; Ramli; Syaad Afifuddin (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
The community service program aims to improve production efficiency and add value to the Tunas Baru Farmer Group in Denai Sarang Burung Village, Deli Serdang, North Sumatra. The farmer group faces challenges in separating rice and rice husk due to their reliance on mobile rice milling services (odong-odong). Through the provision of a rice milling machine, this program helps enhance the quality of rice and utilize the husk as animal feed, ultimately providing a positive impact on the sustainability of agricultural production and the household economy of the farmers.